Psychometry: Cutting-Off Points and Standardization of the Jefferson Empathy Scale Adapted for Students of Kinesiology - Alejandro Reyes-Reyes (SAGE Publishing, 2021)
Currently, the most common measurement of empathy is obtained using scales that offer a continuum between a minimum and a maximum value. The objectives of this study were to establish a norm and estimate cut-off points that would make it possible to assess the Jefferson Scale of Empathy (JSE) version for Health Professions students (HPS-version), and to determine its psychometric properties in Chilean physical therapy students. A secondary analysis was done on a data set from three schools of physical therapy ([ n  = 850], 412 women [48.5%], and 438 men [51.5%]), applying confirmatory factor analysis (CFA) and hierarchical cluster analysis. A CFA replicated the original three-factor model of empathy with sufficiently fit the data. A hierarchical cluster analysis yielded four categories for the level of empathy: high, medium-high, medium-low, and low. Multi-group analyses supported the assumption of a gender-invariant factor structure. Results confirmed the reliability of the global scale (α = .835), and the Perspective Taking (α = .732), Compassionate Care (α = .842), and Walking in Patient’s Shoes (α = .686) dimensions. The instrument made it possible to establish four ordinal categories in the level of students’ empathy. We conclude that the HPS-version of the JSE has adequate psychometric properties; namely validity, reliability, and cut-off points that justify administering it to Chilean physical therapy students.